Updating the Competency Profile and Examination Blueprint for Entry-Level Optometry in Canada - Cane, David; Penny, Margaret; Marini, Anthony; Hynes, Tami (Canadian Journal of Optometry, 2018)
The Optometry Examining Board of Canada (formerly Canadian Examiners in Optometry) is a not-for-profit corporation that administers the entry-to-practice examination for optometrists in Canada in service to its members, the 10 provincial optometry regulators. The described work resulted in an updated entry-level competency profile for optometry, together with an examination blueprint based upon indicators derived from the competencies. The project took place over the period May 2014 – September 2015 and involved the following steps: Establishment of project teams Clarification of conceptual framework Development of proposed competencies Validation of competencies Development of indicators for each competency, consistent with the assessment methodologies used in the entry-to-practice examination Construction of an updated examination blueprint